A COMPARATIVE STUDY OF THE COGNITIVE SEMATICS OF THE BASIC TASTE WORDS "SOUR,SWEET,BITTER AND SALTY" IN CHINESE AND THAI - อดิเรกวุฒิกุล, ศิรินทร์ (Chinese Language and Culture Journal, 2021)
ABSTRACT Every country cannot reduce the "diet" part, and then this article thinks that diet is the reason that brings beauty and happiness to the people. It is a relatively special type of vocabulary in Chinese and Thai languages. Everyone has different experience of taste, and taste words can express the culture and way of thinking of each country. This article studies the original and extended meanings, as well as the cultural connotations of the Chinese and Thai taste words "sour", "sweet", "bitter" and "salty", as well as the cultural connotation. The content of this article can be divided into three parts: Definition of Taste words, The semantic characteristics of taste in Chinese language and in Thai language , The comparison of the meanings of taste between Chinese language and Thai language, this article hopes to have a deeper understanding of taste words, and the study of taste words will also be of great help to the understanding of the language and culture between China and Thailand. Keyword: Chinese and Thai; taste; Word Meaning; Contrast